List of Scolytinae and Platypodinae (COLEOPTERA: Curculionidae) captured by ethanol-baited traps in a tropical rainforest in southern Sabah, Malaysia - Evahtira Gunggot; Roger A Beaver; Jonathan Jimmey Lucas; Sandra Geogina George; Anastasia Rasiah; Wilson VC Wong; Maria Lourdes T Lardizabal; Naoto Kamata (The University of Tokyo Forests, 2025)
Bark beetles (sensu lato) are found in the two subfamilies (Scolytinae and Platypodinae) of the family Curculionidae (Coleoptera) and ecologically diverse and economically important groups. The subfamily Platypodinae includes c. 1,500 species and almost all of these are ambrosia beetles (Peris et al., 2021). On the other hand, c. 6,100 species have been recorded for the subfamily Scolytinae (Cognato et al., 2021), which includes many feeding guilds such as phloem feeders (bark beetles (sensu stricto)), fungal feeders (ambrosia beetles), pith feeders, fruit and seed feeders, and others